Investigation on the Usage of Optimum Content of Graphite Oxide for Bitumen Modification - Lam, Hou Jazz (2015)
This research project involves the preparation of Graphite oxide (GO) and used as a bitumen modifier to understand the effects of GO on the empirical testing and morphological properties of the GO modified bitumen. Graphite Nano fiber was used in the preparation of GO by using Simplified Room Temperature Hummer’s Method. There are six samples prepared in this project which are virgin bitumen, 0.1125 wt. %, 0.15 wt. %, 0.225% wt. % 0.3 wt. % and 0.4 wt. % GO modified bitumen. These six samples are analyzed by conducting Empirical Test such as Penetration Test, Softening Point Test and Ductility Test where the pure bitumen acts as reference material. On the other hand, Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were conducted to know the morphological properties and spectroscopic analysis of the GO Modified Bitumen compared to the pure bitumen.